Availability and social determinants of community health management service for patients with chronic diseases: An empirical analysis on elderly hypertensive and diabetic patients in an eastern metropolis of China. Issue 1 (1st March 2015) - Wu, Zhijun; Jian, Weiyan
Abstract : Objective: This study aimed to determine the availability of community health management services and the relevant social determinants for elderly patients with chronic diseases. Methods: All data were obtained from the 2013 random sampling household survey on an elderly population conducted by the School of Public Health of Peking University in an eastern metropolis in China. Information from the database of the above survey involving 1495 hypertensive or diabetic patients ≥60 years of age, as representatives of the city, were included. The study described the availability of follow-up services by community doctors among elderly hypertensive and diabetic patients during the 12 months before the survey. An ordinal multinomial logistic regression model was used to conduct the analysis on the influence of socio-economic background upon such availability. Results: Eighty-one percent of hypertensive patients and 84.7% of diabetic patients had not received any follow-up service from community doctors within 12 months prior to the survey. Among elderly hypertensive patients, those registered as non-agricultural household members, those with high and above-average income, as well as management personnel of government agencies, enterprises, and social programs have a greater chance of accepting follow-up service by community doctors because of their relatively higher socio-economic rankings. Among elderly diabetic patients, such socio-economic factors had no significant influence on the availability of the follow-up service for chronic diseases. Conclusion: The coverage of community health management services for elderly hypertensive and diabetic patients needs improvement. More effort should focus on promoting the availability of community health management services for elderly hypertensive patients, especially those with lower socio-economic status.